Curcumins-Rich Curry Diet and Pulmonary Function in Asian Older Adults - Ng, Tze Pin (Public Library of Science, 2012)
BACKGROUND: Research on the effects of dietary nutrients on respiratory health in human populations have not investigated curcumin, a potent anti-oxidant and anti-inflammatory compound present principally in turmeric used in large amounts in Asian curry meals. OBJECTIVES: To examine the association of curry intake with pulmonary function among smokers and non-smokers. DESIGN: The frequency of curry intake, respiratory risk factors and spirometry were measured in a population-based study of 2,478 Chinese older adults aged 55 and above in the Singapore Longitudinal Ageing Studies. RESULTS: Curry intake (at least once monthly) was significantly associated with better FEV(1) (b = 0.045±0.018, p = 0.011) and FEV(1)/FVC (b = 1.14±0.52, p = 0.029) in multivariate analyses that controlled simultaneously for gender, age, height, height-squared, smoking, occupational exposure and asthma/COPD history and other dietary or supplementary intakes. Increasing levels of curry intake (‘never or rarely’, ‘occasional’, ‘often’, ‘very often’) were associated with higher mean adjusted FEV(1) (p for linear trend = 0.001) and FEV(1)/FVC% (p for linear trend = 0.048). Significant effect modifications were observed for FEV(1) (curry* smoking interaction, p = 0.028) and FEV(1)/FVC% (curry*smoking interaction, p = 0.05). There were significantly larger differences in FEV(1) and FEV(1)/FVC% between curry intake and non-curry intake especially among current and past smokers. The mean adjusted FEV(1) associated with curry intake was 9.2% higher among current smokers, 10.3% higher among past smokers, and 1.5% higher among non-smokers. CONCLUSION: The possible role of curcumins in protecting the pulmonary function of smokers should be investigated in further clinical studies.